Low Annexin A1 level in HTLV-1 infected patients is a potential biomarker for the clinical progression and diagnosis of HAM/TSP - Bárbara Brasil Santana; Maria Alice Freitas Queiroz; Rodrigo Arcoverde Cerveira; Claudia Mendonça Rodrigues; Ednelza da Silva Graça Amoras; Carlos Araújo da Costa; Maisa Silva de Sousa; Ricardo Ishak; Luiz Ricardo Goulart; Antonio Carlos Rosário Vallinoto (BMC Infectious Diseases, 2021)
Abstract Background Human T-lymphotropic virus 1 (HTLV-1) is etiologically associated with the chronic inflammatory neurodegenerative disease HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP) Annexin A1 (AnxA1) is an anti-inflammatory protein with proposed neuroprotective and anti-neuroinflammatory functions. We hypothesized that ANXA1 gene expression may be dysregulated in HTLV-1-infected HAM/TSP patients. Methods This study involved 37 individuals infected with HTLV-1, including 21 asymptomatic (AS) carriers and 16 with HAM/TSP, and a control group of 30 individuals negative for HTLV-1 and HTLV-2. For AS HTLV-1-positive and HAM/TSP patients, ANXA1 and formyl peptide receptor (FPR1, FPR2 and FPR3) expression and HTLV-1 proviral load (PVL) in peripheral blood cells were evaluated by real-time quantitative PCR (qPCR), and plasma AnxA1 levels were determined by enzyme-linked immunosorbent assay (ELISA). Results ANXA1 gene expression was increased in the AS group compared with the HAM/TSP and control groups, but the differences were not statistically significant. FPR1 gene expression was higher in patients with HTLV-1 than in controls (AS, p = 0.0032; HAM/TSP, p < 0.0001). Plasma AnxA1 levels were higher in the AS group than in the HAM/TSP group (p = 0.0045), and PVL was higher in patients with HAM/TSP than in AS individuals (p = 0.0162). The use of a combined ROC curve using Annexin 1 levels and proviral load significantly increased the sensitivity and specificity to predict progression to HAM/TSP (AUC = 0.851 and AUC = 0.937, respectively, to AUC = 1000). Conclusions Our results suggest that AnxA1 may be dysregulated in HAM/TSP patients. Serological detection of AnxA1 in association with proviral load may provide a prognostic biomarker for HTLV-1-associated neurodegenerative disease.